2006
DOI: 10.1038/sj.onc.1210080
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hypoxic cell death by APIP-induced sustained activation of AKT and ERK1/2

Abstract: Apaf-1-interacting protein (APIP) was previously isolated as an inhibitor of mitochondrial cell death interacting with Apaf-1. Here, we report a hypoxia-selective antiapoptotic activity of APIP that induces the activation of AKT and extracellular signal-regulated kinase (ERK)1/2. Stable expression of APIP in C2C12 (C2C12/APIP) cells suppressed cell death induced by hypoxia and etoposide. Unlike etoposide, however, APIP induces the sustained activation of AKT and ERK1/2 and the phosphorylation of caspase-9 duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
2
27
1
Order By: Relevance
“…3D). The data confirmed previous reports (31,36) of APIP inhibiting apoptosis and revealed a role in inhibition of pyroptosis.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3D). The data confirmed previous reports (31,36) of APIP inhibiting apoptosis and revealed a role in inhibition of pyroptosis.…”
Section: Resultssupporting
confidence: 91%
“…Others have reported that MTA can both inhibit and increase apoptosis depending on the cell type (50,51). Published studies showing APIP inhibition through binding to APAF-1 (31) and regulation of protein phosphorylation (36) provide alternative mechanisms where APIP could regulate apoptosis independent of its role in methionine salvage. For the regulation of apoptosis by APIP, multiple mechanisms are likely involved with their relative importance determined by cell type, metabolic state, and specific stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the weak up-regulation of APIP and UACA mRNA expression, the expression of serpinB9 mRNA was strongly induced in several ADC-treated NSCLC cell lines (Rousalova et al, unpublished data). It has been reported that ischemia/hypoxia up-regulates the expression of APIP in some tissues and tumour cells (25)(26)(27). Although there is evidence that the microenvironment of NSCLC tumours contains many ischemic regions characterized by hypoxia and acidosis (43), we frequently observed decreased expression of APIP mRNA and protein in NSCLC tumours.…”
Section: Discussioncontrasting
confidence: 50%
“…APIP, which is a cytosolic protein, binds to the CARD domain of Apaf-1 and prevents PC-9 recruitment to the apoptosome (25,26). Moreover, during hypoxic conditions, APIP induces sustained activation of AKT and ERK1/2 kinases, which directly phosphorylate PC-9 to inhibit its activation in the apoptosome (27). UACA/nucling, showing both cytoplasmic and perinuclear/nuclear localization (28)(29)(30), interacts with Apaf-1 and induces its translocation into the nucleus upon proapoptotic stress (31).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia was achieved by culturing the cells in MEM (Invitrogen) in an air-tight Plexiglass chamber with GasPak Plus (BD Biosciences) (38) or cells were exposed to hypoxia (0.1% O2) by incubating cells at 37°C in 5% CO 2/10% H2/85% N2 anaerobic incubator (Forma Scientific). Cells were then placed under normoxic conditions.…”
mentioning
confidence: 99%